Praktik Pengungkapan Modal Intelektual pada Perusahaan Publik di BEJ - BAMBANG PURNOMOSIDHI (The Indonesian Journal of Accounting Research, 2013)
The objective of this study is to examines the extent to which 84 listed companies are practizing intellectual capital disclosures in their annual reports, both qualitatively and quantitatively. This paper adopts Sveiby (1997) definition of intellectual capital which classified it into internal structure, external structure, and employee competence. A content analysis of 84 copies of 2001, 2002, and 2003 annual reports was carried out. The findings suggest that the incidence of voluntary disclosures of intellectual capital in company report are high qualitatively, but not quantitatively. In addition, the key components of intellectual capital are poorly understood, inadequately identified, inefficeiently managed, and not reported within a consistent framework when reported at all. The level of disclosure of intellectual capital attributes by 84 listed companies was low.